Paraquat Inhalation, a Translationally Relevant Route of Exposure: Disposition to the Brain and Male-Specific Olfactory Impairment in Mice. (29th December 2020) - Anderson, Timothy; Merrill, Alyssa K; Eckard, Matthew L; Marvin, Elena; Conrad, Katherine; Welle, Kevin; Oberdörster, Günter; Sobolewski, Marissa; Cory-Slechta, Deborah A
Abstract: Epidemiological and experimental studies have associated oral and systemic exposures to the herbicide paraquat (PQ) with Parkinson's disease. Despite recognition that airborne particles and solutes can be directly translocated to the brain via olfactory neurons, the potential for inhaled PQ to cause olfactory impairment has not been investigated. This study sought to determine if prolonged low-dose inhalation exposure to PQ would lead to disposition to the brain and olfactory impairment, a prodromal feature of Parkinson's disease. Adult male and female C57BL/6J mice were exposed to PQ aerosols in a whole-body inhalation chamber for 4 h/day, 5 days/week for 4 weeks. Subsets of mice were sacrificed during and after exposure and PQ concentrations in various brain regions (olfactory bulb, striatum, midbrain, and cerebellum) lung, and kidney were quantified via mass spectrometry. Alterations in olfaction were examined using an olfactory discrimination paradigm. PQ inhalation resulted in an appreciable burden in all examined brain regions, with the highest burden observed in the olfactory bulb, consistent with nasal olfactory uptake. PQ was also detected in the lung and kidney, yet PQ levels in all tissues returned to control values within 4 weeks post exposure. PQ inhalation caused persistent male-specific deficits in olfactory discrimination. No effects were observed in females. These data support the importance of route of exposure in determination of safety estimates for neurotoxic pesticides, such as PQ. Accurate estimation of the relationship between exposure and internal dose is critical for risk assessment and public health protection.